Evaluation of Genetic Diversity among Naga Chili (Capsicum chinense Jacq.) Samples Available in Bangladesh (Plant Tissue Culture and Biotechnology, 2025)
Naga chili possesses a unique aroma and pungency level. Due to its diversified fruit morphology and uses, it has a special acceptance among consumers. Present experiments were designed to evaluate the genetic divergence of morphologically diverged twelve samples collected from three divisions (Barishal, Khulna and Sylhet) of Bangladesh employing the PCR-based RAPD technique. Analysis by seven decamer primers resulted in 33 RAPD loci ranging from 300 bp to 5000 bp with 84.84% polymorphism. Indicating a high polymorphism existed among those samples. The distance matrix and UPGMA dendrogram showed a considerable level of genetic divergence from 0.0589 to 0.8318 in those samples.  This result indicates that the samples collected from the different division are genetically diverged. This outcome can play a vital role in future molecular analysis of Naga chili.Plant Tissue Cult. & Biotech. 34(2): 133-140, 2024 (December)